Poor performance in mathematics among senior secondary school students: Lessons for education planners and parents - Bah, Yahya Muhammed (International Journal of Education and Learning, 2022)
Education is one of the best tools to transform lives and living conditions especially with science and technology. Over the years, governments and families have been trying to ensure children access quality, relevant and affordable education. In the areas of science and technology particularly at tertiary levels, possessing strong mathematical knowledge and skills is a must. However, though the precise number is yet to be documented, children have been woefully failing the subject causing fears and panics in the general population more especially in the parents and government authorities as the future of development seemingly anchored on science and its applications. The fundamental rationale for the systematic literature review is to examine the causes of poor performance in mathematics among senior secondary school students; share knowledge to spark and inspire a process that will usher in appropriate interventions in eradicated the menace. A systematic review of the literatures using information collected from different sources was actuated. Google search engine, google scholar, web of science, scopus database, etc. were used to search for these articles. During the search numerous combinations of words and phrases were used to ensure articles reflect the most recent knowledge and scholarly works. In essence, only peer-reviewed articles published after 2000 were selected except extracts perceived to be of fundamental mileage to the study. However, articles published by staunch international organizations working in education for years and has produced indefatigable knowledge in the field were stealthily appraised. The study revealed that the causes of poor performance in mathematics among senior secondary school students are multifaceted and include causes located in personal status, erroneous beliefs, students, teachers, teaching methods, language competence, teaching and learning materials, parents and family members, schools, policies, society, infrastructures, and government. The poor performance in mathematics among senior secondary school students is negatively impacting their access to tertiary institutions for higher education in order to effectively take part in future national developments and worse of all pushing them to commit crimes as they cannot secure jobs in the highly competitive job market..